Inhibition of H3K9me2 Reduces Hair Cell Regeneration after Hair Cell Loss in the Zebrafish Lateral Line by Down-Regulating the Wnt and Fgf Signaling Pathways - Tang, Dongmei; Lin, Qin; He, Yingzi; Chai, Renjie; Li, Huawei (Frontiers in Molecular Neuroscience, 2016)
The activation of neuromast supporting cell (SC) proliferation leads to hair cell (HC) regeneration in the zebrafish lateral line. Epigenetic mechanisms have been reported that regulate HC regeneration in the zebrafish lateral line, but the role of H3K9me2 in HC regeneration after HC loss remains poorly understood. In this study, we focused on the role of H3K9me2 in HC regeneration following neomycin-induced HC loss. To investigate the effects of H3K9me2 in HC regeneration, we took advantage of the G9a/GLP-specific inhibitor BIX01294 that significantly reduces the dimethylation of H3K9. We found that BIX01294 significantly reduced HC regeneration after neomycin-induced HC loss in the zebrafish lateral line. BIX01294 also significantly reduced the proliferation of neuromast cells and led to fewer SCs in the lateral line. In situ hybridization showed that BIX01294 significantly down-regulated the Wnt and Fgf signaling pathways, which resulted in reduced SC proliferation and HC regeneration in the neuromasts of the lateral line. Altogether, our results suggest that down-regulation of H3K9me2 significantly decreases HC regeneration after neomycin-induced HC loss through inactivation of the Wnt/β-catenin and Fgf signaling pathways. Thus H3K9me2 plays a critical role in HC regeneration.